2013
DOI: 10.1016/j.jped.2013.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and lethality of laboratory-confirmed bloodstream infection caused by non-skin contaminant pathogens in neonates

Abstract: Surgical procedures and CVC usage were significant risk factors for LCBI. Therefore, prevention practices for safe surgery and CVC insertion and manipulation are essential to reduce these infections, in addition to training and continuing education to surgical and assistance teams.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 29 publications
0
10
0
6
Order By: Relevance
“…18 Premature infants are at increased risk of infection because of immature immune function, 4 invasive procedures including placement and subsequent use of central venous lines, 19 mechanical ventilation, and parenteral nutrition. A point prevalence analysis found that 11% of NICU patients had a nosocomial infection, and 50% of those were BSI.…”
Section: Discussionmentioning
confidence: 99%
“…18 Premature infants are at increased risk of infection because of immature immune function, 4 invasive procedures including placement and subsequent use of central venous lines, 19 mechanical ventilation, and parenteral nutrition. A point prevalence analysis found that 11% of NICU patients had a nosocomial infection, and 50% of those were BSI.…”
Section: Discussionmentioning
confidence: 99%
“…(5,7,16,17) At the NICU where the study was developed, figures for late sepsis were less expressive.…”
Section: Discussionmentioning
confidence: 99%
“…(20) The occurrence of late neonatal sepsis and its relation with the NICU environment and the invasive procedures the infants are submitted to have been widely discussed in studies undertaken in the large urban centers of Brazil and internationally. (5,7,8,17,19,21) This concern targets improvements in the quality of care for low-weight infants, reducing the sequelae of clinical problems provoked by intense infection processes and death rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,21,22 Data from seven Brazilian NICUs showed that the incidence of bloodstream infection associated with vascular catheter varies by birth weight: 34.9/1,000 vascular catheter (VC) days in premature infants weighing < 1,000 g, 20.4/1,000 VC days in premature infants weighing between 1,001-1,500 g, 17.3/1,000 VC days in those weighing between 1,501-2,500 g and, 18.1/1,000 VC days in infants weighing > 2,500 g. 23 These rates are much higher than those found in the National Healthcare Safety Network (NHSN), which shows rates of 4.4/1,000 VC days in those weighing < 1,000 g, 4.8/1,000 VC days between 1,001-1,500 g, 4.2/1,000 VC days between 1,501-2,500 g. and 3.1/1,000 VC days in those weighing > 2,500 g, and reinforce the importance of catheter-associated infection in this environment and the need for preventive measures against this condition of concern. 5, 24,25 In the questionnaire on vascular catheters, it was observed that only two-thirds of the centers have a PICC insertion and maintenance team, with this representing an aspect to be improved, which can be crucial as a LOS prevention strategy. The other catheter care procedures were similar between centers.…”
Section: Discussionmentioning
confidence: 99%